Effect of air temperature in indoor transition spaces on the thermal response of occupant during summer - Tian Zhong; Xi Meng (Scientific Reports)
Abstract During the hot summer months, the significant temperature disparity between outdoor and indoor air-conditioned spaces can lead to thermal discomfort and pose a potential health risk. Transition areas such as corridors and elevator lobbies, serving as intermediary zones connecting indoors and outdoors, have been found effective in mitigating this thermal discomfort. In this study, three different temperatures (25 °C-case 1, 27 °C-case 2, and 29 °C-case 3) were employed to investigate the dynamic physiological regulation and thermal perception response of individuals when transitioning from an outdoor environment into an indoor neutral room through a transition space. The findings revealed that mT sk decreased by 0.31 °C, 0.13 °C, and 0.07 °C; TSV decreased by 1.63, 1.56, and 0.9 units; while TCV increased by 1.9, 2.16 ,and 0.81units for cases1-3 respectively indicating that an air temperature of around 27 °C is most suitable for achieving optimal comfort levels in these transition spaces. The correlation between UTCI index with MTSV was stronger compared to PET or SET* throughout the entire process; moreover, a better linear relationship was observed between ΔTSV and ΔT than ΔTCV. Furthermore, a second-order polynomial function model was established using dissatisfaction rate at initial entry moment into new environment along with operative temperature difference, resulting in acceptable temperatures ranging from 25.3 °C to 27.93 °C within current experimental conditions.